Foxc2 and BMP2 Induce Osteogenic/Odontogenic Differentiation and Mineralization of Human Stem Cells from Apical Papilla. (25th July 2018) - Zhang, Wen; Zhang, Xiaolei; Li, Junyuan; Zheng, Jianmao; Hu, Xiaoli; Xu, Meng; Mao, Xueli; Ling, Junqi
Abstract : As a transcription factor regulated by bone morphogenetic protein 2 (BMP2), Forkhead c2 (Foxc2) plays a pivot role in osteogenesis/odontogenesis. However, the role of Foxc2 and BMP2 in regulating osteo-/odontogenic differentiation and mineralization of stem cells from apical papilla (SCAP) is still uncertain. In this research, overexpression of Foxc2 gene significantly improved the proliferation of SCAP four days and eight days after transfection, but overexpression of both Foxc2 and BMP2 genes significantly inhibited the proliferation of SCAP eight days after transfection. RT-qPCR and western blot results indicated that SCAP-Foxc2-BMP2 significantly upregulated osteo-/odontogenic genes and proteins at most of the time points in SCAP after transfection. Moreover, SCAP-Foxc2-BMP2 formed notably more alkaline phosphatase-positive and alizarin red-positive mineralized nodules than other three group cells sixteen days after transfection. In conclusion, our findings revealed that Foxc2 and BMP2 synergistically promoted osteo-/odontogenic differentiation and mineralization of SCAP in vitro .